PHENOLIC AND FLAVONOID PRODUCTION, PHYTOCHEMICAL PROFILE, AND ANTIOXIDANT CAPACITY OF Adenostemma platyphyllum AT DIFFERENT CONCENTRATIONS OF HYDROPONIC SOLUTIONS : Produksi Fenolik dan Flavonoid, Profil Fitokimia, dan Kapasitas Antioksidan Adenostemma platyphyllum pada Konsentrasi Larutan Hara Hidroponik Berbeda - Trivadila; Tamsin, Aqlia Hanna Nurfatiha; Batubara, Irmanida; Ridwan, Taopik; Aziz, Sandra Arifin (Universitas Tidar, 2023)
Adenostemma platyphyllum is considered a weed with various benefits but has not been widely cultivated. This work aims to obtain the optimum concentration of a nutrient solution (AB-mix) to produce optimum phenolic and flavonoid levels, antioxidant capacity and metabolite profiling in A. platyphyllum using a hydroponic wick system. Different AB-mix nutrient solution concentrations were employed in a one-factor randomized block design. The highest total phenolic, flavonoid concentrations and antioxidant capacity were found in plants without additional nutrient solutions. However, the highest phenolic and flavonoid productivity was found in plants with a nutrient solution concentration of 1100 mg/L. The phenolic/flavonoid group compounds were successfully identified by separating the components using thin-layer chromatography. The intensity of the bands produced from each treatment was quite varied. The untreated plant produced thicker phenolic/flavonoid bands than the other treatments. This was supported by the heatmap pattern produced by the untreated ones, which had high color intensity. Therefore, the optimum concentration of nutrient solution to produce optimum phenolic, flavonoid levels, and antioxidant capacity in A. platyphyllum cultivation by hydroponic wick system was the concentration of 1100 mg/L.